2017
DOI: 10.1002/rcm.7873
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of a Knudsen effusion mass spectrometer sampling system

Abstract: This code allows the geometry (aperture spacing and diameters) of the sampling system to be optimized for maximum transmission. The calculated effusate distributions and low average number of orifice wall collisions illustrated the advantages of restricted collimation. Calculated transmission factors are also compared to literature values calculated via the analytical method of Chatillon and colleagues. Published in 2017. This article is a U.S. Government work and is in the public domain in the USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The original results presented in the paper by Nuta and Chatillon [1] showed that the transmission yield varied with the location of the emission plane relative to the effusion orifice entrance. Recently, however, Radke et al [3] calculated, using the Monte Carlo method, the transmission probability for the Knudsen cell collimation device that they used in their mass spectrometric method and their results agreed with the formulae proposed by Morland et al [2] Thus, we have returned to our calculations, checking first that our published equations [1] remained correct, and we have found an error resulting from the transcription of Eqn. (12) from this paper to the computer, specifically for the parameter H 1 .…”
supporting
confidence: 70%
“…The original results presented in the paper by Nuta and Chatillon [1] showed that the transmission yield varied with the location of the emission plane relative to the effusion orifice entrance. Recently, however, Radke et al [3] calculated, using the Monte Carlo method, the transmission probability for the Knudsen cell collimation device that they used in their mass spectrometric method and their results agreed with the formulae proposed by Morland et al [2] Thus, we have returned to our calculations, checking first that our published equations [1] remained correct, and we have found an error resulting from the transcription of Eqn. (12) from this paper to the computer, specifically for the parameter H 1 .…”
supporting
confidence: 70%
“…Molecular flow can be modeled analytically 55,56 or simulated using a Monte Carlo technique. 39,[57][58][59][60][61] Today, Monte Carlo is probably the most useful technique. A valid simulation can be run on a desktop computer, and a number of factors can be easily explored.…”
Section: Molecular Beammentioning
confidence: 99%
“…This is shown in Figure 7. According to the nomenclature of Chatillon, the aperture in the copper plate is the “field aperture,” and the aperture adjacent to the ionizing region is the “source aperture.” The geometry of the NASA Glenn system is shown in Figure 8A, and modeling parameters (aperture spacing and orifice diameters) are shown in Figure 8B 61 . Chatillon et al have derived equations for the flux through these different apertures based on the analogy of light transmission between two disks, which decreases inversely with the square of the distance between the two disks 68,69 .…”
Section: Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations